2009
DOI: 10.1187/cbe.08-09-0054
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis of Student Questions in a Cell Biology Laboratory

Abstract: Asking questions is an essential component of the practice of science, but question-asking skills are often underemphasized in science education. In this study, we examined questions written by students as they prepared for laboratory exercises in a senior-level cell biology class. Our goals were to discover 1) what types of questions students asked about laboratory activities, 2) whether the types or quality of questions changed over time, and 3) whether the quality of questions or degree of improvement was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…If the instructor can readily generate high‐level questions well beyond 50, asking the students for 50 is fine; if the instructor struggles to generate 50 good questions because the reading is too simple, change the reading or reduce the number of questions. Use repeated class activities to discuss the different levels of questions to help students identify low‐ and high‐level questions, and to lead students to reflect on the power of complex questions in discussing important issues. Helping students to ask better questions may require specific activities (Keeling et al, 2009). Provide a checklist for students to use when evaluating their references.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the instructor can readily generate high‐level questions well beyond 50, asking the students for 50 is fine; if the instructor struggles to generate 50 good questions because the reading is too simple, change the reading or reduce the number of questions. Use repeated class activities to discuss the different levels of questions to help students identify low‐ and high‐level questions, and to lead students to reflect on the power of complex questions in discussing important issues. Helping students to ask better questions may require specific activities (Keeling et al, 2009). Provide a checklist for students to use when evaluating their references.…”
Section: Discussionmentioning
confidence: 99%
“…Use repeated class activities to discuss the different levels of questions to help students identify low‐ and high‐level questions, and to lead students to reflect on the power of complex questions in discussing important issues. Helping students to ask better questions may require specific activities (Keeling et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Questions are an important part of the ongoing scientific research process and have an important educational role (Biddulph, Symington, & Osborne, 1986;Brill & Yarden, 2003;Keeling, Polacek, & Ingram, 2009;Scardamalia & Bereiter, 1992). However, it is difficult to use children's questions in a classroom setting, as they are frequently a negligible component of general classroom learning.…”
Section: Research Approachmentioning
confidence: 99%
“…An honest and sincere question asked by students to dig information is proof that students are deeply involved in the learning (Walsh & Sattes, 2011). However, the question asked by the students was still underemphasized (Keeling et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to Cardoso & Almeida (2014), 73.3% of questions created by students in Photosynthesis (N=258) learning were modest questions. Keeling et al (2009) reported that in science education Cell Biology laboratory, 81% of the student wrote LOT questions, and 19% of the student wrote HOT items.…”
Section: Introductionmentioning
confidence: 99%